The birthday storm / 2. - Draper, Sharon M. (Sharon Mills) (Draper, Sharon M. (Sharon Mills). Sassy., 2009)
Sassy and her family go to Florida during summer vacation to visit Grammy for her birthday, and when the weather takes a turn for the worse, Sassy learns that love is more important than decorations and caterers.